2021
DOI: 10.1039/d1na00125f
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled synthesis of cyclodextrin-capped gold nanoparticles for molecular recognition using surface-enhanced Raman scattering

Abstract: Cyclodextrin (CD)-capped gold nanoparticles (AuNPs) can be applied in sensing, catalysis, and self-assembly processes due to their molecular recognition ability. As plasmon resonance of AuNPs depends on their size, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It is reported that π–Au interactions between PAHs and Au surfaces are negligible under ambient conditions. In other words, PAHs are difficult to adsorb spontaneously to Ag and Au nanoparticles. The critical issues were the chemical modification and surface oxidation of the Ag and Au nanoparticle surface. ,, So far, there have been extensive computational and experimental studies showing that π–metal interactions on Au surfaces exist under ideal or nearly ideal circumstances where the metal crystal planes are exposed, well-defined, and placed under high vacuum to minimize the barriers to adsorption (Figure A) .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that π–Au interactions between PAHs and Au surfaces are negligible under ambient conditions. In other words, PAHs are difficult to adsorb spontaneously to Ag and Au nanoparticles. The critical issues were the chemical modification and surface oxidation of the Ag and Au nanoparticle surface. ,, So far, there have been extensive computational and experimental studies showing that π–metal interactions on Au surfaces exist under ideal or nearly ideal circumstances where the metal crystal planes are exposed, well-defined, and placed under high vacuum to minimize the barriers to adsorption (Figure A) .…”
Section: Resultsmentioning
confidence: 99%
“…Organic dyes bound to solid surfaces via weak interactions (such as van der Waals' forces, π-stacking, etc. ) can display unpredictable optical/electronic behaviour, such as fluorescence enhancement/quenching, plasmon resonance enhanced fluorescence, 66 surface-enhanced Raman scattering (SERS), 67 and enhanced photo-induced catalytic ability, 68 etc. Such a hybrid material can be applied to specific applications in high-resolution imaging, analysis technologies and photocatalysis for energy conversion.…”
Section: The Optical Physical Properties Of Aggregated Pyrenesmentioning
confidence: 99%
“…Nowadays, it has been reported that metal nanoparticles can be effectively stabilized with cyclodextrins to inhibit their aggregation. 24 Notably, β-Cyclodextrin (β-CD) with hydrophilic outer layers and hydrophobic cavity has been employed to encapsulate size-matched guest contaminants in solution. 25 Liu et al have indicated that the β-CD-modified catalyst exhibits moderate binding affinity, which facilitates the preferential accumulation of substrates and serves as a bridging agent between guest pollutants and the catalyst, thereby reducing the migration distance of pollutants to the catalyst surface.…”
Section: Introductionmentioning
confidence: 99%